Solar-driven device resilience in extreme terrestrial environments - Ding,T; Liu,X; Yang,X; Xu,Y; Cao,XE (Cell Reports Physical Science, 2026)
Summary Solar-driven chemical conversion systems offer scalable solutions for energy storage and water purification, yet their performance remains constrained by the controlled laboratory conditions in which they are tested. Deployment in extreme terrestrial environments (ETEs), characterized by thermal extremes, intermittent light, and fluctuations in photon flux, requires a shift from material-centric optimization to holistic device resilience. Herein, we propose a framework based on three core principles: kinetic decoupling, temporal bridging, and operational intelligence. When flexibly integrated, these strategies enable hybrid platforms to reach DTI 3–4 and chart a path toward scalable deployment (DTI-5). We advocate standardized translational metrics to quantify robustness and highlight future integration across terrestrial, marine, and extraterrestrial domains.